G3P2A0 Hamil 26 Minggu Inpartu dengan Perdarahan Trimester II e.c Mola Hidatidosa Parsial Janin Tunggal Hidup Intrauterin - Riska Putri Soraya; Muhammad Caesario Liazmi; Nurul Islamy (Medula, 2022)
Hydatidiform mole is an abnormal condition in pregnancy with part or all of the chorionic villi undergo hydropic degeneration. Hydatidiform mole is divided into complete hydatidiform mole and partial hydatidiform mole. The incidence rate in Indonesia is around 1:80 normal deliveries. While the incidence of partial moles is rare, the incidence varies from 5:100,000 and 1:10,000 pregnancies. Mrs. A 37 years old came to the ER Abdul Moeloek Hospital with complained abdominal pain and vaginal bleeding. Result of general examination: moderate ill appearance, blood pressure was 148/89 mmHg, other sign examination were within normal limits. On obstetric examination, the uterine fundal height was two fingers above the umbilicus, the fetal heart rate was 155x/min and three contractions in 10 minutes, the duration was 20-40 seconds. Speculum examination result : opened portio, there is a fish eyed-like bubble, and active bleeding. Ultrasound examination revealed that she was pregnant 26 weeks with a partial hydatidiform mole. Complete blood count with severe anemia. Whereas immunological and serological examinations results: β-hCG 5,242,880 mIU/mL; T3 1.93 nmol/L; T4 157, 43 nmol/L; TSH 0.01 uIU/mL. So the diagnosis is G3P2A0 26 weeks of gestational age in active phase with a partial hydatidiform mole accompanied by hyperthyroidism and severe anemia with single live fetus intrauterine. Patient lead to spontaneous vaginal delivery were then treated with curettage, transfusion and postpartum care. Furthermore, the mole tissue was taken for Anatomical Pathology examination and the patient was planned to control for the β-hCG evaluation.